1992
DOI: 10.1099/0022-1317-73-5-1065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of a spike protein of neurovirulent murine coronavirus JHMV variant c1-2

Abstract: A cDNA encoding the spike (S) protein of the neurovirulent murine coronavirus JHMV variant cl-2 was isolated and sequenced. Analysis of the cDNA revealed that the S protein consists of 1376 amino acids, as does the S protein of mouse hepatitis virus 4. We inserted the cDNA into the genome of vaccinia virus to obtain a recombinant vaccinia virus (rVV). The S protein expressed in RK13 cells infected by the rVV was shown to be electrophoretically and immunologically indistinguishable from the S protein produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…In addition, the S1 subunit is relatively variable among MHV; deletions and mutations often occur in the hypervariable region (22,31,62). When compared with the S protein of MHV-4, there are three deletions of one, three, and eight amino acid residues in Yamada's MHV-2 strain (31,42,53) and a large deletion of 141 and 153 amino acid residues in the fusion-positive MHV-JHM strain and our fusion-negative MHV-2 strain, respectively, in the hypervariable region of the S1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the S1 subunit is relatively variable among MHV; deletions and mutations often occur in the hypervariable region (22,31,62). When compared with the S protein of MHV-4, there are three deletions of one, three, and eight amino acid residues in Yamada's MHV-2 strain (31,42,53) and a large deletion of 141 and 153 amino acid residues in the fusion-positive MHV-JHM strain and our fusion-negative MHV-2 strain, respectively, in the hypervariable region of the S1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the regions of the S protein structure responsible for its biological functions, it is necessary to express the functional S protein in the absence of other virus-related proteins. Thus, we have previously expressed the entire S protein in cultured mouse cells, using recombinant VV, and showed that the expressed S protein had antigenic and fusogenic properties indistinguishable from those of the authentic S protein (Taguchi et al, 1992;, although the S protein expressed by baculovirus in our laboratory was shown to be similar but not identical to the authentic S protein (Yoden et al, 1989). To study further the regions on the S protein involved in the biological functions, we have expressed the S 1 and $2 subunits of the S protein in a system in which they showed no apparent difference in antigenicity and intracellular transport compared with the authentic S proteins.…”
Section: Discussionmentioning
confidence: 99%
“…All of these plasmids were confirmed to be correctly constructed for the expected S protein-coding regions by dideoxynucleofide chain termination sequencing (Sanger et al, 1977). For expression of the entire S protein of cl-2, we have used the vaccinia virus transfer vector (VV-TV), pSFcl2-S whose construction has been previously described (Taguchi et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations